MIPSeR: An Application for Malaysia Island Packages and Services Reservation - Khoo, Pei Li; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2022)
Island is part of tourism that contributes to financial development in Malaysia. Island lovers are currently facing problems when they need to find island packages at various platforms like Google Search, Facebook and Twitter to look for island packages and prices. This makes island travellers hard to compare the package prices and package contents. These people lack a system that collects and summarizes all information about island packages in Malaysia. Customization of island travelling package is provided within the proposed system to make island trip more feasible. People do not know how to reach the islands, start planning for an island trip, ask for assistance trip plan, and customize an island travelling package. In this application, travellers can search for all island travelling packages offered by the west coast islands of Peninsular Malaysia and Borneo Coasts Islands in Malaysia. This application provides travellers with a good experience of island travelling where they can review comments from previous travellers travelling to those islands on the East Coast of Peninsular Malaysia and islands in Borneo Coasts in Malaysia. It aims to assist island lovers by providing a platform for them to view and purchase island packages by recognised buyers or agents. The prototyping method is selected to implement the whole system as buyers or users can see steady progress in planning, analysis, design and developing and then implementing. The development of the application depends fully on user requirements and will only proceed to the next phase if there is no objection. At the end of the project development, it is shown that the application has successfully been developed and the objectives have been achieved.